Shielding Design for the PGNAA Experimental Facility at Kartini Reactor - T. Sutondo; S Syarip (PPIKSN-BATAN, 2018)
Two steps of preliminary study had been conducted in conjunction with the design of a PGNAA experimental facility at Kartini reactor, i.e. beam characterization of the existing beam ports to select one going to be used and the collimator design at the selected beam port. This paper presents the results of the following study concerning with the radiation shielding design at the outer area, in front of the beam port exit, where the experiments will be conducted. MCNPX was used for the purpose of simulations, which included the design of neutron beam catcher and the outer shield. Based on the assumed source terms, the materials being used, and the geometrical arrangements, it is concluded that by using paraffin of 60 cm thickness for the beam catcher and 50 cm for the concrete of the outer shield would be sufficient to reduce the radiation dose below the maximum recommended limit.